Perbedaan Pemahaman Siswa Tentang Sopan Santun Ditinjau Dari Pemberian Layanan Bimbingan Kelompok Berlandaskan Falsafah Dandang Tingang Kelas VII SMP Muhammadiyah Palangkaraya: Student Understanding Differences About Politeness Viewed From Giving Group Guidance Services Based On Falsafah Dandang Tingang Class VII Of SMP Muhammadiyah Palangkaraya - Dewi Rabiola; Muhammad Andi Setiawan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to determine whether there is a difference in understanding of Student Polite regarding the provision of Group Guidance Services based on the Dandang Tingang Philosophy. This study used the Pure Experimental Research approach. The design used is the pretest-posttest control group design. Based on the results of research conducted at Palangka Raya Muhammadiyah Middle School with the results of the calculation of paired sample test with t count on the results of the Pre-test the value of t = 1,088 ≥ and t table 2,10 which shows no difference between the control group and the experimental and postal results -test value t = 5.696 ≥ and t table 2.10 price t count ≥ t table so that Ho is rejected, and Ha is accepted it can be said if the experimental group gets better results compared to the control group. In the results of the Pre-test which showed no difference between the experimental and control groups and after being given treatment through group guidance services in the experimental group, the results of the post-test showed there were differences between the control and experimental groups. It can be concluded if the implementation of group guidance services in the experimental class is effective in increasing the understanding of students manners.